Financial Sector Assessment Program Update : India - IAIS Insurance Core Principles - International Monetary Fund (World Bank, Washington, DC, 2013)
This assessment of India's compliance with the International Association of Insurance Supervisors (IAIS) Insurance Core Principles (ICP) was carried out as part of the 2011 Financial Sector Assessment Program (FSAP). Although this is the second FSAP for India, this is the first external assessment of India's compliance with the ICPs. The Insurance Regulatory and Development Authority (IRDA) have principal responsibility for insurance regulation and supervision in India, although the central government also has some reserve supervisory powers. This assessment is based upon information made available to the assessor in preparation for and during the June 2011 FSAP mission. The assessment has also been informed by discussions with regulators and market participants. The assessment employs the 2003 version of the IAIS insurance core principles and methodology and is based on the essential criteria (EC) listed in that document.